Analisis Faktor Pada Faktor-Faktor Yang Mempengaruhi Stres Guru SD Selama Sistem Pembelajaran Daring Era Covid-19 (Studi Kasus di SD Kecamatan Padang Timur) - Fadilah, Dinda; Rosha, Media (UNIVERSITAS NEGERI PADANG, 2022)
Stress is one of the effects that arise due to the covid-19 pandemic, one of which is experienced by teachers at the elementary school level. This can happen because at the elementary school level, if it is seen from students who are only 7-12 years old, who are still ordinary in terms of using technology, elementary school teachers feel more difficult to carry out online learning process. The purpose of this study is to find out what factors significantly affect the stress of elementary school teachers in the subdistrict of Padang Timur during the online learning system in the covid-19 era. This type of study was an applied study with the spread of the questionnaire among 88 respondents selected using the random sampling cluster method. The results of the study were obtained by seven factors that influenced the stress of elementary school teachers in the subdistrict of Padang Timur during the covid-19 online learning system including educational factors, learning implementation factors, teacher's information technology skills factors, learning process and assessment factors, family factors, the low motivation for students' learning and media factors for online learning.